2019
DOI: 10.1021/acsanm.9b01377
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-Bridged Chitosan-Eudragit S-100 Nanoparticles for Colorectal Cancer

Abstract: Covalently bonded Eudragit S-100 (EU) and chitosan (CS) based colon-specific nanoparticles (CSE NPs) were fabricated as drug carriers for treating colorectal cancers through oral administration. Thiolation of EU and CS prevents the usage of the cross-linking agent. This gives an advantage over the shortcomings of existing EU- and CS-based delivery systems that are associated with large sized nanoparticles with a broad range of size distribution. Paclitaxel (PTX)-loaded CSE NPs presented an efficacy of 8–10% af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“… Polysaccharide Delivery system Drug/payload molecule Therapeutic application Feature Ref. Chitosan Chitosan-capped enzyme-responsive hollow mesoporous silica nanoplatforms Doxorubicin Not mentioned in the literature Bacterial enzyme sensitive 192 Chitosan Eudragit S-100 and chitosan-based nanoparticles Paclitaxel Colorectal cancer Sustained release, pH responsive, bacterial enzyme sensitive and cancer-targeted 193 Amphipathic chitosan derivative Amphiphilic chitosan derivatives and cell-penetrating peptides modified nanoparticles Insulin Lowering the blood glucose The bacterial enzyme sensitive delivery and the use of cell-penetrating peptides 194 Chondroitin sulfate Tablets coated by Surelease® and chondroitin sulfate Dapsone Not mentioned in the literature Time-dependent and bacterial enzyme sensitive 195 Dextran The doxorubicin and superparamagnetic iron oxide nanoparticles-loaded solid lipid nanoparticle coated with folate and dextran Doxorubicin and superparamagnetic iron oxide nanoparticles Colon cancer The microbial enzyme sensitive and tumor-targeted delivery system used for chemo/magnetothermal combination therapy 196 Guar gum The guar gum modified upconversion nanocomposite 5-Fluorouracil Colorectal cancer Bacterial enzyme sensitive and NIR triggered 197 Guar gum Transformable capsules containing indomethacin immediate-release pellets Indomethacin Colon cancer Bacterial enzyme sensitive 198 Guar gum Microspheres Mesalamine and synbiotics Ulcerative colitis Bacterial enzyme sensitive 199 Guar gum 5-Flurouracil-containing mesoporous silica nanoparticles with guar gum capping 5-Flurouracil …”
Section: The Influence Of the Gut Microbiota On The Drug Delivery System Designmentioning
confidence: 99%
“… Polysaccharide Delivery system Drug/payload molecule Therapeutic application Feature Ref. Chitosan Chitosan-capped enzyme-responsive hollow mesoporous silica nanoplatforms Doxorubicin Not mentioned in the literature Bacterial enzyme sensitive 192 Chitosan Eudragit S-100 and chitosan-based nanoparticles Paclitaxel Colorectal cancer Sustained release, pH responsive, bacterial enzyme sensitive and cancer-targeted 193 Amphipathic chitosan derivative Amphiphilic chitosan derivatives and cell-penetrating peptides modified nanoparticles Insulin Lowering the blood glucose The bacterial enzyme sensitive delivery and the use of cell-penetrating peptides 194 Chondroitin sulfate Tablets coated by Surelease® and chondroitin sulfate Dapsone Not mentioned in the literature Time-dependent and bacterial enzyme sensitive 195 Dextran The doxorubicin and superparamagnetic iron oxide nanoparticles-loaded solid lipid nanoparticle coated with folate and dextran Doxorubicin and superparamagnetic iron oxide nanoparticles Colon cancer The microbial enzyme sensitive and tumor-targeted delivery system used for chemo/magnetothermal combination therapy 196 Guar gum The guar gum modified upconversion nanocomposite 5-Fluorouracil Colorectal cancer Bacterial enzyme sensitive and NIR triggered 197 Guar gum Transformable capsules containing indomethacin immediate-release pellets Indomethacin Colon cancer Bacterial enzyme sensitive 198 Guar gum Microspheres Mesalamine and synbiotics Ulcerative colitis Bacterial enzyme sensitive 199 Guar gum 5-Flurouracil-containing mesoporous silica nanoparticles with guar gum capping 5-Flurouracil …”
Section: The Influence Of the Gut Microbiota On The Drug Delivery System Designmentioning
confidence: 99%
“…5 Over the past ten years, the importance of ERS100, a synthetic polymer with a pH verge of more than 7, has grown in the field of medicinal formulations. 6 Some of the features that make ERS100 a reliable choice for treating colorectal malignancies are gut targeting and value in sustained drug release. We have the possibility to improve the efficacy of drug therapy and transition to an oral route of drug administration by combining ERS100 with SA nanoparticulate systems.…”
Section: Introductionmentioning
confidence: 99%
“…[34,185] Chang et al developed thiolated alginate-based nanoparticles with improved colonic targeting potential, demonstrated by a marked increase in drug release in a colonic pH mimic and reducing fluid. [34] Providing a highly effective tool in the targeted treatment of colon cancer and inflammatory bowel disease, other research groups have followed and established thiolate alginate-based nanocarriers for budesonide, docetaxel, and doxorubicin [186,187] In addition, paclitaxel (PTX)-loaded NPs based on chitosan-Eudragit S-100 with disulfide bond (CSE NP) were developed by Sood et al [188] After 48 h of treatment of HCT116 colon cancer cells, they observed a uniform distribution of PTX within the cells and a significant accumulation in the G2/M phase after 24 h, indicating the arrest of cell division during the mitotic phase. In subsequent in vivo biodistribution studies in male Balb/C mice, a retention of NPs in the colonic region up to 24 h after oral administration provided strong evidence for colon-specific targeting.…”
Section: Drug Deliverymentioning
confidence: 99%